PERAN BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN ROKOK MARLBORO DI KOTA MEDAN - Owen de Pinto Simanjuntak; Esther Praja Anggriany Panggabean (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
One of the factors that influence purchasing decisions by consumers is the marketing mix. This study aims to determine how much influence the marketing mix has on the decision to purchase Marlboro cigarettes in the city of Medan. The form of this research uses a quantitative description with the aim of finding out how much influence the X variable, namely the marketing mix, has on the Y variable, namely the purchasing decision. With this method, it is hoped that researchers can explain existing phenomena based on data and information obtained from research. From the results of simple linear regression calculations obtained Y = 4.603 + 0.411X means that if the marketing mix is ​​constant then there will be a purchase decision of 4.603 and if the marketing mix is ​​increased 1 time then the purchasing decision will increase by 0.411. Testing the adjusted coefficient of determination (R square) obtained a value of 0.254, meaning that the independent variable, namely the marketing mix, has an effect of 25.4% on purchasing decisions and 74.6% is influenced by other variables such as product quality, customer service, loyalty and organizational culture.